Mapping the evolution consumer trust and security concerns in e-wallet research: a bibliometric and thematic review - Rahmat Hidayat; Wardayani Wardayani; Ihsan Iskandar; Nurhayati Nurhayati; Dewi Shinta Wulandari Lubis (Forum Kerjasama Pendidikan Tinggi, 2026)
This research aims to map the development of the literature on e-wallets, by examining the growth of publications, influential sources and documents, the contributions of authors, institutions and countries, collaboration patterns, and the conceptual structures that shape the field. The study used a bibliometric approach to 283 English-language articles selected from 683 Scopus documents through the PRISMA procedure. Metadata was analyzed using Biblioshiny and VOSviewer through indicators of scientific production, citations, authorship networks, country collaboration, and co-occurrence of keywords with a minimum limit of three occurrences. The results show that e-wallet publications have increased sharply since 2018 and reached the highest level in the 2023-2025 period. Malaysia, Indonesia, and India are the main contributors, with Malaysia having the strongest productivity and international collaboration network. The mapping of 71 keywords resulted in nine clusters that affirmed the multidisciplinary nature of the e-wallet study, including data security, privacy, trust, technology acceptance, user behavior, cashless payments, fintech, financial inclusion, and banking innovation. Although the knowledge network is growing densely, scientific collaboration is still dominated by publications in one country. Future research suggests combining Scopus with Web of Science, Dimensions, or other databases; expand search terms; and complement bibliometrics with systematic reviews and cross-border empirical studies. The next study needs to prioritize cybersecurity, privacy protection, artificial intelligence, blockchain, digital literacy, and intergenerational behavioral differences in various regulatory and cultural contexts.